2012
DOI: 10.1038/eye.2012.89
|View full text |Cite
|
Sign up to set email alerts
|

High molecular weight hyaluronan decreases oxidative DNA damage induced by EDTA in human corneal epithelial cells

Abstract: Purpose To investigate the toxic effects of ethylenediaminetetraacetic acid disodium salt (EDTA), a corneal penetration enhancer in topical ophthalmic formulations, on DNA in human corneal epithelial cells (HCEs), and to investigate whether the effect induced by EDTA can be inhibited by high molecular weight hyaluronan (HA). Methods Cells were exposed to EDTA in concentrations ranging from 0.00001 to 0.01% for 60 min, or 30 min high molecular weight HA pretreatment followed by EDTA treatment. The cell viabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…Apart from regulating cytokine release, hyaluronan itself can protect cells from apoptosis by scavenging reactive oxygen species. This has been shown in cultured corneal epithelial cells and keratinocytes treated with either UV radiation or toxic substances (75,76). Furthermore, Wang and co-workers (77) showed that high levels of hyaluronan and Has2 expression were associated with resistance to UVB radiation and serum starvation in mouse fibroblasts.…”
Section: Discussionmentioning
confidence: 78%
“…Apart from regulating cytokine release, hyaluronan itself can protect cells from apoptosis by scavenging reactive oxygen species. This has been shown in cultured corneal epithelial cells and keratinocytes treated with either UV radiation or toxic substances (75,76). Furthermore, Wang and co-workers (77) showed that high levels of hyaluronan and Has2 expression were associated with resistance to UVB radiation and serum starvation in mouse fibroblasts.…”
Section: Discussionmentioning
confidence: 78%
“…The benefits of EDTA in inhibiting MMPs have been previously reported . However, this substance commonly used as a preservative and corneal penetrating enhancer in ophthalmic solutions induces oxidative DNA damage in the corneal cells at high concentrations . The high concentration used herein (1%) may have caused the significant larger ulcerated area observed at the 6‐h time point following corneal injury, in association with a higher area under the curve in the EDTA treatment group.…”
Section: Discussionmentioning
confidence: 68%
“…Our experiment failed to show benefits of any tested agent in decreasing the levels of MMP‐2 and MMP‐9 after corneal alkali injury in rats. Despite the possible toxic corneal effects of EDTA and N‐acetylcysteine have been previously discussed herein, they may have acted only in acute phases of the corneal healing, once the corneal epithelium surface tended to appear restored at the end of the study.…”
Section: Discussionmentioning
confidence: 84%
“…There have been literatures reported that a preincubation of HMW-HA could protect corneal epithelial cells against oxidative damage induced by ultraviolet B [24, 25], benzalkonium chloride [22, 40], EDTA [41], sodium lauryl sulfate [26], and so on. In the present study, we confirmed the protective role of 0.2% 1000 kDa HA against genotoxicity of Cr(VI) on HCE cells.…”
Section: Discussionmentioning
confidence: 99%